ANALISIS POTENSI SUMBER DAYA ALAM DALAM MENDUKUNG KESEJAHTERAAN MASYARAT DI DESA KAMOT KECAMATAN ALOR TIMUR LAUT - Marta Simey Famau; Yulistina Maro; Paulina Lambila; Petru Mau Tellu Dony (JOURNAL OF COMMUNITY DEDICATION, 2026)
This study aims to identify and analyze the potential of natural resources in Kamot Village, East Alor District, and to examine their contribution to improving community welfare. The research employed a qualitative method with an ethnographic approach through interviews and field observations. The results show that Kamot Village possesses five main natural resource sectors with high potential, namely agriculture, plantations, livestock, inland fisheries, and forestry. In the agricultural sector, wet and dry land areas serve as the basis for food production with main commodities such as rice, corn, cassava, and various vegetables. The plantation sector provides the largest contribution through commodities such as candlenut, cashew, cocoa, coffee, tamarind, and vanilla, supported by relatively large land areas. The livestock sector has also developed with a considerable number of animals, providing economic benefits for the community. In addition, inland fisheries, particularly catfish cultivation, show promising business prospects through group-based management systems. The forestry sector, which covers approximately 50% of the village area, functions as an ecosystem buffer and produces high-value non-timber forest products such as vanilla, coffee, candlenut, and porang. Overall, the natural resource potential of Kamot Village is substantial and diverse; however, its management remains traditional and faces challenges including limited water availability, technology constraints, and lack of technical assistance. This study recommends strengthening community capacity, developing appropriate technology, and implementing sustainable management practices to optimize the utilization of natural resources and improve community welfare.